2013
DOI: 10.1159/000348519
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Fluoride Concentration and Activity against Virulence Factors and Viability of a Cariogenic Biofilm: in vitro Study

Abstract: Despite widespread use of various concentrations of fluoride for the prevention of dental caries, the relationship between fluoride concentration and activity against cariogenic biofilms has not been much studied. Herein we investigated the relationship between fluoride concentration and activity against virulence factors and viability of Streptococcus mutans biofilms. S. mutans biofilms were formed on saliva-coated hydroxyapatite discs. The 70-hour-old biofilms were exposed to 0, 1, 3, 10, 30, 100, 300, 1,000… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
41
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 30 publications
3
41
1
1
Order By: Relevance
“…These findings indicate that 1-min fluoride treatment neither exerts bactericidal activity nor affects the bacterial biovolume of S. mutans biofilms. This confirmed the findings of a previous study that demonstrated that 2-hour fluoride treatment did not show biofilm bactericidal activity at 2,000 ppm F - [Pandit et al, 2013].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These findings indicate that 1-min fluoride treatment neither exerts bactericidal activity nor affects the bacterial biovolume of S. mutans biofilms. This confirmed the findings of a previous study that demonstrated that 2-hour fluoride treatment did not show biofilm bactericidal activity at 2,000 ppm F - [Pandit et al, 2013].…”
Section: Discussionsupporting
confidence: 92%
“…However, according to a previous study, even low concentrations (10 ppm F -) of fluoride affected the virulence properties and composition of S. mutans biofilms [Pandit et al, 2011b]. Furthermore, the half maximum effective concentration (EC 50 ) against the virulence properties of S. mutans biofilms ranged from 3.07 to 24.7 ppm F - [Pandit et al, 2013]. The difference in antivirulence concentration of fluoride between the present and previous studies can be attributed to differences in treatment duration.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…mutans UA159 (ATCC 700610; serotype c) biofilms were formed on saliva-coated hydroxyapatite (sHA) discs (2.93 cm 2 ; Clarkson Chromatography Products, Inc., South Williamsport, Pa., USA) placed in a vertical position in 24-well plates, as detailed elsewhere [Pandit et al, 2013]. Briefly, the sHA discs were prepared by incubation with filter-sterilized (0.22-μm low proteinbinding filter) human saliva for 1 h at 37 ° C. For biofilm formation, the sHA discs were transferred to a 24-well plate containing 1% sucrose (w/v) ultrafiltered (10 kDa molecular weight) tryptone yeast extract broth with S. mutans UA159 (2-5 × 10 6 colony-forming units, CFU/ml).…”
Section: S Mutans Biofilm Preparation and Fluoridementioning
confidence: 99%
“…1 a). After treatment, the biofilms were dip-washed twice with salt solution (50 m M KCl + 1 m M MgCl 2 , pH 7.0) and incubated in filter-sterilized saliva (pH 7.3) for 0, 6, 12, 25, 50, or 100 min at 37 ° C. After incubation, biofilm pH drop assays were performed as described elsewhere [Belli et al, 1995;Pandit et al, 2013]. Briefly, the treated 46-hour-old biofilms were transferred to a 6-well plate containing salt solution.…”
Section: S Mutans Biofilm Preparation and Fluoridementioning
confidence: 99%